2020
DOI: 10.4103/jehp.jehp_182_19
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of electronic education and workshop on the satisfaction of nurses about Emergency Severity Index triage

Abstract: INTRODUCTION: Nurse educators need to develop the level of scientific and practical of the students with the goal of becoming expert nurses. However, the use of modern educational methods to raise the motivation and satisfaction of learners can help individuals achieve this goal. Therefore, the aim of this study was to investigate the effect of health education in emergency nurses about triage. METHODS: A two-group pool-blind experimental study was performed on seventy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Also, the results of the present study showed that the operating room nurses participating in each training course were delighted with the use of electronic and levelled education approaches. Learners' satisfaction is one of the essential factors in the effectiveness of new educational processes (33,34,44). Nurses' satisfaction with the education process leads to improved learning motivation and, as a result, improves their level of knowledge (44).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, the results of the present study showed that the operating room nurses participating in each training course were delighted with the use of electronic and levelled education approaches. Learners' satisfaction is one of the essential factors in the effectiveness of new educational processes (33,34,44). Nurses' satisfaction with the education process leads to improved learning motivation and, as a result, improves their level of knowledge (44).…”
Section: Discussionmentioning
confidence: 99%
“…Learners' satisfaction is one of the essential factors in the effectiveness of new educational processes (33,34,44). Nurses' satisfaction with the education process leads to improved learning motivation and, as a result, improves their level of knowledge (44). The results of Lhbibani et al's study (2022) showed that the satisfaction of nurses in the intervention group (using the e-learning approach) was signi cantly higher than the nurses in the control group (using face-to-face mock training method) (P < 0.05) (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 13 14 ] Growing tendency toward e-learning suggests the numerous advantages of this methods compared to the other conventional education approaches. [ 15 16 ] The challenges of e-learning in Iran are expressed in the form of 5 approaches electronic, teaching, curriculum development, and psychological and cultural approaches. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%